Meningkatkan Kreativitas Anak Usia 5-6 Tahun Melalui Penggunaan Media Bahan Alam - Husnatul Mar'ataini; Muazar Habibi; Ika Rachmayani; I Made Suwasa Astawa (Indonesian Publication Center, 2021)
Creativity will not grow if children do not get support from the surrounding environment. The creativity of preschool children cannot be separated from the factor at play. In this research, natural media was used as a children's play media. The purpose of this research is to increase the creativity of 5-6 years old children through the use of natural from the environment’s media in Montong Betok Village, Montong Gading District, East Lombok in 2020. The type of the research is descriptive qualitative, the research does not make calculations and aims to describe creativity children and natural from the environment’s media. The research object was three children aged 5-6 years. Data collection methods used are qualitative methods to collect data using participant observation and transcription techniques. The data analysis method in this research is descriptive technique with a qualitative approach, the results of the study are not in the form of numbers but in the form of sentences. The results of this research obtained data, that the use of natural media can increase the creativity in children aged 5-6 years old. In this research, the steps taken were to invite children to carry out creative activities on their own according to their existing ideas and imagination, provide motivational guidance and encouragement to children, provide opportunities for children to be more active and creative in a pleasant learning atmosphere, being open and appreciative of interests and ideas.